Micro/nanostructured Bi2Mn4O10 with hierarchical spindle morphology as a highly efficient anode material for lithium‐ion batteries. Issue 10 (21st June 2022) - Cheng, Cuixia; Cheng, Yinfang; Lai, Guosong
Abstract: Mullite‐type compound Bi2 Mn4 O10 has shown the feasibility as anodes of next lithium‐ion batteries (LIBs). Herein micro/nano‐Bi2 Mn4 O10 with hierarchical spindle‐like architectures has been successfully synthesized using a one‐step hydrothermal method without any no surfactant or template. A time‐dependent experiment is carried out to observe the morphology evolution, suggesting a nucleation–aggregation/growth–dissolution–recrystallization process. As anode of LIBs, the as‐prepared spindle‐shaped micro/nano Bi2 Mn4 O10 harvests a significantly high initial discharge capacity of 1022 mA h g −1 at 1 C, an excellent cyclability performance (563.8 mA h g −1 after 400 cycles), a better high‐rate capability (100 mA h g −1 at 10 C), quick diffusion kinetics (1.8 × 10 −12 cm 2 s −1 ), and low active energy (19.5 kJ mol −1 ), which are significantly superior to that of its bulk counterparts and the previous reports. The encouraging lithium storage performance largely stems from the synergistic effect of the unique spindle‐shaped micro/nanostructure.